The Effect of Audit Fee, Auditor Rotation, Auditor Firm Reputation, and Auditor Specialization on Audit Quality - Rochmatilah, Siti; Susanto, Barkah; Purwantini, Anissa Hakim (JIFA (Journal of Islamic Finance and Accounting), 2021)
The purpose of this research was analyze the influence of audit fee, audit switching, audit firm reputation and auditor specialization on audit quality. Data in the current research were secondary data obtained from the financial statements of consumer good industry companies listed on the Indonesia Stock Exchange in the period 2017-2019. This study used purposive sampling method to select sample from the population. Based on method, obtained 26 companies with 78 samples. Data was analyzed using the multiple regression analysis. Proxy measurements for audit quality is using discretionary accruals Kaznik model (1999). The result showed that the audit switching give impact on audit quality. While audit fee, audit firm reputation and auditor specialitation do not impact on audit quality.Keywords: Audit Fee, Audit Switching, Audit Firm Reputation, Auditor Specialization, Audit Quality.